Robot Beroda Multifungsi dengan Lengan 4 Servo Berbasis Kontrol Nirkabel Joystik PS2 - Danang Hendrawan; Muhammad ‘Atiq; Yohanes Tri Novia Putra; Rizal Agri Wahyuadi; Raka Dian Mahardi; Sigit Prakosa A N (Jurnal Publikasi Teknik Informatika, 2025)
In the ever-increasing development of technology, the field of robotics has become one of the most promising fields, both in the industrial world, education, and technological research. Robotics not only increases work efficiency, but also encourages innovation in various sectors. This project aims to develop a multi-purpose wheeled robot equipped with a 4 servo mechanical arm, which functions to support the robot's operational capabilities in various simple tasks such as picking up and moving objects. The main objective of this project is to understand and implement a robotic control system using an Arduino Uno microcontroller, an L298N motor driver, and integration with a wireless PS2 control interface. In more detail, this research aims to: (1) build a four-wheeled robot that can be controlled wirelessly using a PS2 controller; (2) implement a 4 servo arm system as an additional actuator to enhance the robot; and (3) integrate hardware components such as an Arduino Uno and an L298N motor driver into a robot control system. The methodology in this research includes the hardware and software design stages, programming using the Arduino IDE, and integration of all components such as DC motors, SG90 servos, wireless PS2 control modules, and power supplies. Testing was conducted to observe the system's response to input from the controller. The implementation results show that the robot can operate stably. The robot is able to respond to commands well and accurately, both in terms of basic movements using wheels and in moving its servo arm. The implementation results show that the robot can operate stably. The robot is able to respond to commands well and accurately, both in terms of basic movements using wheels and in moving its servo arm.